Genome sequencing in cytogenetics: Comparison of short‐read and linked‐read approaches for germline structural variant detection and characterization. Issue 3 (27th January 2020) - Uguen, Kévin; Jubin, Claire; Duffourd, Yannis; Bardel, Claire; Malan, Valérie; Dupont, Jean‐Michel; El Khattabi, Laila; Chatron, Nicolas; Vitobello, Antonio; Rollat‐Farnier, Pierre‐Antoine; Baulard, Céline; Lelorch, Marc; et al.
Abstract: Background: Structural variants (SVs) include copy number variants (CNVs) and apparently balanced chromosomal rearrangements (ABCRs). Genome sequencing (GS) enables SV detection at base‐pair resolution, but the use of short‐read sequencing is limited by repetitive sequences, and long‐read approaches are not yet validated for diagnosis. Recently, 10X Genomics proposed Chromium, a technology providing linked‐reads to reconstruct long DNA fragments and which could represent a good alternative. No study has compared short‐read to linked‐read technologies to detect SVs in a constitutional diagnostic setting yet. The aim of this work was to determine whether the 10X Genomics technology enables better detection and comprehension of SVs than short‐read WGS. Methods: We included 13 patients carrying various SVs. Whole genome analyses were performed using paired‐end HiSeq X sequencing with (linked‐read strategy) or without (short‐read strategy) Chromium library preparation. Two different bioinformatic pipelines were used: Variants are called using BreakDancer for short‐read strategy and LongRanger for long‐read strategy. Variant interpretations were first blinded. Results: The short‐read strategy allowed diagnosis of known SV in 10/13 patients. After unblinding, the linked‐read strategy identified 10/13 SVs, including one (patient 7) missed by the short‐read strategy. Conclusion: In conclusion, regarding the results of this study, 10X Genomics solution did not improve the detection and characterization of SV. Abstract : We compared linked‐read and short‐read sequencing in patients with structural variants. We conclude that linked‐read strategy did not improve the detection and characterization of structural variants.